2020
DOI: 10.1016/j.finel.2020.103438
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamic response of reinforced concrete beams subjected to drop weight impact

Abstract: To improve the impact resistance of reinforced concrete structures, a detailed understanding of the dynamic response is required. This study investigates this impact resistance using experiments in combination with 3D non-linear finite element (FE) simulations. The experiments made use of high-speed photography and digital image correlation (DIC), while a damage-plasticity constitutive model for concrete was used in the FE simulations. Drop weight impact tests of simply supported reinforced beams made of plain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…GOM Correlate software [32] was used in the present research for the post-processing of the images. Some authors [33][34][35] have discussed on how to define the facet mesh and post-processing key parameters for an appropriate DIC analysis of impact tests. In the present research, the facet size employed to obtain punctual displacements is 20 and 40 px (32.8 and 65.6 mm) for the falling mass and beam, respectively.…”
Section: Testing Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…GOM Correlate software [32] was used in the present research for the post-processing of the images. Some authors [33][34][35] have discussed on how to define the facet mesh and post-processing key parameters for an appropriate DIC analysis of impact tests. In the present research, the facet size employed to obtain punctual displacements is 20 and 40 px (32.8 and 65.6 mm) for the falling mass and beam, respectively.…”
Section: Testing Configurationmentioning
confidence: 99%
“…In addition, some of the points were employed as reference to define digital extensometers just in the locations where shear cracks developed. As full-field strain diagrams are a useful method to assess the crack development with the help of DIC [33], a triangular mesh with a facet size of 20 px and a distance between mesh points of 9 px (14.76 mm) was employed to understand the crack evolution. In addition, it is possible to obtain other parameters (such as strains) by postprocessing the mesh displacements.…”
Section: Testing Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…The PPSRC beam–column joint is constituted of concrete and steel, so it is also rate-sensitive. When subjected to dynamic loadings, the response characteristics and damage mechanism of the PPSRC beam–column joint will show obvious differences from that subjected to static or quasi-static loadings [ 34 ]. However, knowledge of the strain rate effect on the dynamic behavior of the PPSRC beam–column joint is limited, with emphasis primarily placed on the observed material dynamic mechanical properties and less attention paid to changes in the dynamic behavior of the PPSRC beam–column joint.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…At present, in view of the problem that RC structures are prone to brittleness under impact loads, some researchers have increased the toughness of components by adding fibers to the concrete. Leppanen et al (2020) conducted numerical simulation of drop hammer impact test on RC beams and fiber reinforced concrete beams. The results showed that the addition of fiber reduced the crack spacing, crack width and mid-span deflection of the beam, while the reinforcement strain tended to be localized, and could be used to predict the risk rate of reinforcement fracture.…”
Section: Introductionmentioning
confidence: 99%